Prudent Rationalizability in Generalized Extensive-Form Games with Unawareness - Aviad Heifetz; Martin Meier; Burkhard Schipper (University of California, Department of Economics, 2019)
We define a cautious version of extensive-form rationalizability for generalized extensive-form games with unawareness that we call prudent rationalizability. It is an extensive-form analogue of iterated admissibility. In each round of the procedure, for each tree and each information set of a player a surviving strategy of hers is required to be rational vis-a-vis a belief system with a full-support belief on the opponents' previously surviving strategies that reach that information set. We demonstrate the applicability of prudent rationalizability. In games of disclosure of verifiable information, we show that prudent rationalizability yields unraveling under full awareness but unraveling might fail under unawareness. We compare prudent rationalizability to extensive-form rationalizability. We show that prudent rationalizability may not refine extensive-form rationalizability strategies but conjecture that the paths induced by prudent rationalizable strategy profiles (weakly) refine the set of paths induced by extensive-form rationalizable strategies.
Keywords: C72; D83; 330; Caution; extensive-form rationalizability; unawareness; disclosure; verifiable information; persuasion games; iterated admissibility; common strong cautious belief in rationality